2008
DOI: 10.1080/00048670802050553
|View full text |Cite
|
Sign up to set email alerts
|

Suicide in Psychiatric Patients: Case–Control Study in Singapore

Abstract: Suicidal risk remains high in Singaporean psychiatric patients soon after discharge. They share some common risk factors for suicide identified in Western studies but the lower prevalence of substance abuse and comorbidity in Singaporean suicide subjects was one notable difference. The phenomena of suicides soon after discharge and outpatient review suggest the need for proper identification and more intensive follow up during this period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
2
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 21 publications
2
19
2
6
Order By: Relevance
“…A study from Singapore reported that a considerable percentage of individuals with mental illness committed suicide soon after discharge from a psychiatric hospital, with 15% committing suicide within the first week, 21% within two weeks, 26% within four weeks, and an alarming 63% within one year 45 . These high figures reflect the population studied, of individuals with psychiatric disorders severe enough to require hospital admission.…”
Section: Factors Contributing To Suicidementioning
confidence: 99%
“…A study from Singapore reported that a considerable percentage of individuals with mental illness committed suicide soon after discharge from a psychiatric hospital, with 15% committing suicide within the first week, 21% within two weeks, 26% within four weeks, and an alarming 63% within one year 45 . These high figures reflect the population studied, of individuals with psychiatric disorders severe enough to require hospital admission.…”
Section: Factors Contributing To Suicidementioning
confidence: 99%
“…This is similarly noted among suicide studies from Asia (Cheng et al, 1995;Phillips et al, 2002;Thong et al, 2008). The associated physical illnesses are generally chronic, debilitating, deteriorating, painful and stigmatizing; such as HIV or AIDS, cancers and chronic renal failure (Harris & Barraclough, 1994).…”
Section: Risk Factors In Asiamentioning
confidence: 63%
“…In a Singapore case-control study of suicide in psychiatric patients, psychotic symptoms in the form of auditory hallucinations and delusions were associated with significantly increased risk of suicide (Thong, Su, Chan & Chia, 2008). Alcohol abuse or dependence was present in 44% and 34% of suicide completers in Taiwan (Cheng et al, 1995) and India (Vijayakumar & Rajkumar, 1999) respectively.…”
Section: Risk Factors In Asiamentioning
confidence: 98%
See 1 more Smart Citation
“…[159][160][161][162][163] An analysis of HES data for England carried out in the early stages of this research programme showed that the risk of non-fatal self-harm is similarly elevated in the period after hospital discharge. 164 In total, > 6% of patients discharged from psychiatric inpatient care were admitted to a general hospital bed as a result of self-harm in the subsequent 12 months.…”
Section: Introductionmentioning
confidence: 99%